An Eastern Hepatobiliary Surgery Hospital Microvascular Invasion Scoring System in Predicting Prognosis of Patients with Hepatocellular Carcinoma and Microvascular Invasion After R0 Liver Resection: A Large‐Scale, Multicenter Study. (28th May 2019) - Zhang, Xiu‐Ping; Wang, Kang; Wei, Xu‐Biao; Li, Le‐Qun; Sun, Hui‐Chuan; Wen, Tian‐Fu; Chai, Zong‐Tao; Chen, Zhen‐Hua; Shi, Jie; Guo, Wei‐Xing; Xie, Dong; Cong, Wen‐Ming; et al.
Abstract: Background: Microvascular invasion (MVI) is associated with poor postoperative survival outcomes in patients with hepatocellular carcinoma (HCC). An Eastern Hepatobiliary Surgery Hospital (EHBH) MVI scoring system was established to predict prognosis in patients with HCC with MVI after R0 liver resection (LR) and to supplement the most commonly used classification systems. Materials and Methods: Patients with HCC with MVI who underwent R0 LR as an initial therapy were included. The EHBH‐MVI score was developed from a retrospective cohort from 2003 to 2009 to form the training cohort. The variables associated with overall survival (OS) on univariate analysis were subsequently investigated using the log‐rank test, and the EHBH‐MVI score was developed using the Cox regression model. It was validated using an internal prospective cohort from 2011 to 2013 as well as three independent external validation cohorts. Results: There were 1, 033 patients in the training cohort; 322 patients in the prospective internal validation cohort; and 493, 282, and 149 patients in the three external validation cohorts, respectively. The score was developed using the following factors: α‐fetoprotein level, tumor encapsulation, tumor diameter, hepatitis B e antigen positivity, hepatitis B virus DNA load, tumor number, and gastric fundal/esophageal varicosity. The score differentiated two groups of patients (≤4, >4 points) with distinct long‐term prognoses outcomes (median OS, 55.8 vs. 19.6 months; p < .001). The predictive accuracy of the score was greater than the other four commonly used staging systems for HCC. Conclusion: The EHBH‐MVI scoring system was more accurate in predicting prognosis in patients with HCC with MVI after R0 LR than the other four commonly used staging systems. The score can be used to supplement these systems. Implications for Practice: Microvascular invasion (MVI) is a major determinant of survival outcomes after curative liver resection for patients with hepatocellular carcinoma (HCC). Currently, there is no scoring system aiming to predict prognosis of patients with HCC and MVI after R0 liver resection (LR). Most of the widely used staging systems for HCC do not use MVI as an independent risk factor, and they cannot be used to predict the prognosis of patients with HCC and MVI after surgery. In this study, a new Eastern Hepatobiliary Surgery Hospital (EHBH) MVI scoring system was established to predict prognosis of patients with HCC and MVI after R0 LR. Based on the results of this study, postoperative adjuvant therapy may be recommended for patients with HCC and MVI with an EHBH‐MVI score >4. This score can be used to supplement the currently used HCC classifications to predict postoperative survival outcomes in patients with HCC and MVI. Abstract : This article reports a new EHBH‐MVI scoring system, based on preoperative serological and postoperative pathological data, that was developed with the goal of predicting long‐term survival in patients with hepatocellular carcinoma with microvascular tumor invasion and to identify patients who may benefit from adjuvant therapy based on the prediction of poor postoperative prognosis using the new scoring system.